Application of Culturally Responsive Teaching (CRT) in the Pandhalungan Cultural Context with the Project Based Learning (PjBL) Model In Developing 21st Century Skills for Students at SMP - Nila Maharotunnisa; Muhammad Mukhlis Anshori; Taufikur Rohman Muzekki (STKIP Taman Siswa Bima, 2025)
The application of cultural values is often rarely visible in classroom learning, even though the existence of culture must continue to be preserved. One strategy that is still rarely implemented is integrating culture into the learning process. Therefore, this study aims to explore the importance of implementing culturally responsive teaching, specifically focusing on Pendhalungan culture. This research employs a qualitative approach to deeply understand the learning phenomenon in the context of Class 7E at SMPN 5 Jember. Data were collected through observation, interviews, and documentation. Triangulation of sources and techniques was used to ensure data validity. Data analysis was conducted using the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that Culturally Responsive Teaching (CRT), when combined with Project-Based Learning (PjBL), is effective in developing students' 21st-century skills. The integration of Pendhalungan local culture through projects such as diorama creation, regional songs, and role-playing enhances students' creativity, communication, collaboration, and critical thinking. This approach makes learning more meaningful, strengthens cultural identity, and encourages active participation and social character development among students.